O jogo (da estratégia) já começou!: as configurações da máquina de saber-poder em uma distribuidora de alimentos - Edson Antunes Quaresma Júnior (2016)
Seeking to ensure strategic outcomes, a new mean of managing the distribution units activities is transferred by Company. The purpose of this thesis is inserted in this context, to highlight and describe the update of power-knowledge strategies in a reseller, located in Montes Claros city, in Minas Gerais state. Among these power-knowledges can be listed organizational strategy as theoretical field and the supplier\ reseller strategy as empirical field. Once the first knowledge-powers are part of the studies about organizations, we sought in their initial contacts with Michel Foucault a construction capable of, in connection with Deleuze's interpretation of Foucault's analytical, illuminate a diagrammatic trace, a guide. In the process, that conductor has been found presupposed by knowledges delimiting the organizations ground for the manager, but also the very knowledge of management in the 1970s and 1980s. Hence it is presupposed by contemporary organizations, which are tangent of studies on organizations either through of its dual emphasis on their stars and champions in contrast with the crowds, now through of organizational forms that seek to show the management trend to the collapse. It was noted also that the knowledge of strategy condenses into a managerial, procedural, practical, or "ordinary" form. In face of these initial updates, it was possible, by contrast, perceive a strategy that has as its object the very forces, which separate epistemologically the figures pervading the knowledge of "organizational strategy". These figures that when participate in the everyday, are updated in the reseller "machine" of power-knowledge. The reported plot developed at the moment when the supplier tries to insert a program at this machine, a "game", whose main link is the manager, provided as the activities configurator. From that point, managerial knowledge or not, but self-recurrent, cyclic, the knowledge began to update through of managerialism and tactics. At the end of the study, it was noticed the existence of four alternatives that consider the very forces of affecting and being affected, two of them by the managerialist perspective: set up the machine and adapt to it the knowledge of the game, and innovate by creating better ways to also adapt to it the managerialist knowledge; and two by the ordinary perspective, which remained at the same diagrammatical trait demonstrated in their affecting and being affected condition, but as a state of no legitimacy to the managerialist knowledge: to configure the own game of power-knowledge and send it back by changing the settings of the Companys management form and set up the machine differently of the suggested by the managerialist know but on site. However, it was concluded by a fifth path: the relative to ordinary management, which, by suggesting the focus on discursive objects, this study continues. Thus the ordinary manager cannot have as reference the affect or receiving affection but the sound of emptiness from relational forces of the outside. Surpassing on all the movements, it was realized the primacy of this constant murmur over the other powers: the resistance.